Digital transformation, ESG performance and enterprise innovation - Xiaomeng Liu; Lei Wang (Scientific Reports)
Abstract Humanity has transitioned from the industrial era to the era of the digital intelligence economy. In this context, the Chinese government has emphasized the need to “accelerate the development of the digital intelligence economy and promote its deep integration with the real economy.” For enterprises, this integration fundamentally entails a process of digital intelligence transformation. Simultaneously, ESG performance plays a critical role in enabling this enterprise transformation. Together, digital intelligence transformation and ESG form a synergistic relationship, empowering enterprises to secure a favorable position in innovation-driven competition. Based on a sample of A-share listed companies spanning from 2004 to 2023, this paper empirically investigates the impact of digital transformation and ESG performance on corporate innovation performance. The findings reveal an inverted U-shaped relationship between enterprise digitalization and innovation performance, while ESG performance positively influences innovation performance. Furthermore, digital transformation and ESG performance positively reinforce each other, thereby collectively enhancing enterprise innovation performance.